2004
DOI: 10.1097/01.ico.0000121706.58571.f6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Eye Donation From Postmortem Cases in a Tertiary Care Hospital

Abstract: In our experience, literacy, socioeconomic status, and prior knowledge of eye donation of next kin had no correlation with donor corneal tissue procurement. Active counseling by a motivated team can be effective even in families with no prior knowledge and low socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 9 publications
6
82
0
6
Order By: Relevance
“…[9] In our study 75.2% (170) respondents aged below 40 years are willing to donate their eyes, which is similar to the studies conducted by Patil et al 77.6% ,by Gupta et al 80%,Singh et al(87.2%) [6,20,21] . But it is low (44.3%) inthe study of Tandon et aland Yew et al(67%) [22,23] . Our study found significantly low willingness to donate eyes in higher age group 34%(77),which is similar to that of Priyadarhini et al [4] In contrast,Patil et al and Ronaki et alfound willingness for eye donation is high in higher age group.…”
Section: Discussionmentioning
confidence: 89%
“…[9] In our study 75.2% (170) respondents aged below 40 years are willing to donate their eyes, which is similar to the studies conducted by Patil et al 77.6% ,by Gupta et al 80%,Singh et al(87.2%) [6,20,21] . But it is low (44.3%) inthe study of Tandon et aland Yew et al(67%) [22,23] . Our study found significantly low willingness to donate eyes in higher age group 34%(77),which is similar to that of Priyadarhini et al [4] In contrast,Patil et al and Ronaki et alfound willingness for eye donation is high in higher age group.…”
Section: Discussionmentioning
confidence: 89%
“…In another study willingness for eye donation was seen in 66 (41.5%) whereas 93 (58.5%) females refused eye donation in families of post mortem cases. 9 In the present study 88 (83.02%) had the source of information by television followed by newspaper and friends, 39 (36.79%), 38 (35.85%) respectively. Similar results were shown in the study done by Singh et al 10 which showed 77.8% source by television.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Tandon R et al, showed 159 poten tial donors from 721 Postmortem cases, who had not pledged their eyes for eye donation previously and so concluded that the prior knowledge of eye donation had no influence on willingness for eye donation [6].…”
Section: Discussionmentioning
confidence: 99%